BAP guidelines on the management of weight gain, metabolic disturbances and cardiovascular risk associated with psychosis and antipsychotic drug treatment. (August 2016) - Cooper, Stephen J; Reynolds, Gavin P; ,; Barnes, TRE; England, E; Haddad, PM; Heald, A; Holt, RIG; Lingford-Hughes, A; Osborn, D; McGowan, O; Patel, MX; et al.
Excess deaths from cardiovascular disease are a major contributor to the significant reduction in life expectancy experienced by people with schizophrenia. Important risk factors in this are smoking, alcohol misuse, excessive weight gain and diabetes. Weight gain also reinforces service users' negative views of themselves and is a factor in poor adherence with treatment. Monitoring of relevant physical health risk factors is frequently inadequate, as is provision of interventions to modify these. These guidelines review issues surrounding monitoring of physical health risk factors and make recommendations about an appropriate approach. Overweight and obesity, partly driven by antipsychotic drug treatment, are important factors contributing to the development of diabetes and cardiovascular disease in people with schizophrenia. There have been clinical trials of many interventions for people experiencing weight gain when taking antipsychotic medications but there is a lack of clear consensus regarding which may be appropriate in usual clinical practice. These guidelines review these trials and make recommendations regarding appropriate interventions. Interventions for smoking and alcohol misuse are reviewed, but more briefly as these are similar to those recommended for the general population. The management of impaired fasting glycaemia and impaired glucose tolerance ('pre-diabetes'), diabetes and other cardiovascular risks, such as dyslipidaemia, are also reviewed with respect to other currently available guidelines. These guidelines were compiled following a consensus meeting of experts involved in various aspects of these problems. They reviewed key areas of evidence and their clinical implications. Wider issues relating to primary care/secondary care interfaces are discussed but cannot be resolved within guidelines such as these.